Adaptive Control of Nuclear Reactors using a Digital Computer - Bereznai, George (My University, 1969)
The feasibility of adaptive control of a nuclear reactor is investigated. For practical reasons, an actual operating power plant is chosen, and a digital computer model developed for the reactor and associated control system. The effects of parameter variations on the transient response of the overall system are studied, and the advantages of using an adaptive controller established. An algorithm for the adaptation scheme is developed, and applied successfully to control the nuclear reactor.
Keywords: nuclear reactor; digital computer; adaptive control; power plant